A comparison of fragrance ingredients in green and nongreen detergents. Issue 2 (3rd April 2017) - Zarogianni, Aikaterini-Maria; Loupa, Glykeria; Rapsomanikis, Spyridon
ABSTRACT: Six green (certified with EU Ecolabel), six nongreen household detergents, and two products for professional cleaning were examined for fragrance compounds by gas chromatography coupled to mass spectrometry (GC-MS). The examined detergents are products from multinational companies and best sellers in the Greek market. Only one fragrance ingredient was found in the products for professional applications compared with the 35 in the nongreen products and the 23 ingredients found in green products. Seven ingredients were the same between green and nongreen products. Fragrances are important for marketing purposes but may threaten human health and the environment.